2020
DOI: 10.1063/1.5144991
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric constant and density of aqueous alkali halide solutions by molecular dynamics: A force field assessment

Abstract: The concentration dependence of the dielectric constant and the density of 11 aqueous alkali halide solutions (LiCl, NaCl, KCl, RbCl, CsCl, LiI, NaI, KI, CsI, KF, and CsF) is investigated by molecular simulation. Predictions using eight non-polarizable ion force fields combined with the TIP4P/ε water model are compared to experimental data. The influence of the water model and the temperature on the results for the NaCl brine are also addressed. The TIP4P/ε water model improves the accuracy of dielectric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 99 publications
(148 reference statements)
3
19
0
Order By: Relevance
“…We notice that our value of the simulated dielectric constant using SPC/E is relatively small compared to that found experimentally for pure water (ε = 78.5). However, our results are in good agreement with other studies [30][31][32]. Table 3.…”
Section: Dynamical Propertiessupporting
confidence: 93%
“…We notice that our value of the simulated dielectric constant using SPC/E is relatively small compared to that found experimentally for pure water (ε = 78.5). However, our results are in good agreement with other studies [30][31][32]. Table 3.…”
Section: Dynamical Propertiessupporting
confidence: 93%
“…Fixed point charge water models are limited in some ways by their use of the same partial charges to empirically fit the potential energy landscape and dipole moment, two distinct water properties [44,45]. Inevitably, the choice in water model (many listed in [46,47]) may also dictate the accuracy in (a) solvation, (b) dielectric constant, and (c) dipole moment [44], and affect ionic behavior along with many other properties.…”
Section: Polarization Can Potentially Pose Particular Challengesmentioning
confidence: 99%
“…Fixed point charge water models are limited in some ways by their use of the same partial charges to empirically fit the potential energy landscape and dipole moment, two distinct water properties [44,45]. Inevitably, the choice in water model (many listed in [46,47]) may also dictate the accuracy in (a) solvation, (b) dielectric constant, and (c) dipole moment [44], and affect ionic behavior along with many other properties. Previous work in the Gilson lab indicated that even fixed-charge water models can vary dramatically in water placement and orientation around hosts as well as in thermodynamic properties like the enthalpy of binding [48,49], and it seems likely that polarizable models may exhibit even larger differences.…”
Section: Polarization Can Potentially Pose Particular Challengesmentioning
confidence: 99%
“…In case of Ewald summation, the summation of partial charges to a molecular dipole moment µ i is carried out for each molecule. If a mixture contains ions, which carry a permanent charge, they affect the dielectric constant only through their interactions that alter the orientation of solvent molecules [34]. Fig.…”
Section: Dielectric Constantmentioning
confidence: 99%